PENGARUH POLA ASUH MENGGUNAKAN MEDIA PERMAINAN ULAR TANGGA TERHADAP PENGETAHUAN PENCEGAHAN STUNTING PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS BATURADUA TAHUN 2022 - Rusdiyah Rusdiyah (Universitas Aufa Royhan di Kota Padangsidimpuan, 2022)
Stunting is a condition where children fail to thrive due to malnutrition. Indonesia is included in the third country with the highest prevalence with an average prevalence of stunting in 2005-2017 was 36.4%. One of the prevention efforts to overcome stunting is through health promotion in the form of learning media using of snakes and ladders game. The purpose of this study was to determine the effect of using media on knowledge in preventing stunting in the working area of ​​Baturadua Health Center. The material used is BKB gold which has been prepared previously. The research method uses quasi-experimental. The results of the study found that there was an influence of upbringing using the snakes and ladders media game on the prevention of stunting in pregnant women in the working area of ​​the Baturadua Health Center, so it was recommended to use it because the snakes and ladders simulation method was effectively used by health workers to increase participants' knowledge about stunting prevention. Keywords : stunting, Parenting, Media